Larangan Pernikahan Semarga Dalam Adat Batak di Kabupaten Labuhan Batu Utara Persepektif Teori Konflik George Simmel - Pangestu, Pujo; Asmawi; Muhtadi Anshor, Ahmad (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The Batak community has experienced a shift in the meaning of marriage from the prohibition of surname marriage to an eleutherogamous marriage system that does not recognize the prohibition of surname marriage. This research uses a qualitative approach to understand the relationship between George Simmel's conflict theory and marriage issues in Indonesia, especially in the event of surname marriage in Labuhan Batu Utara. The main focus of this research is how surname marriage causes conflict which is seen as a form of social tension and reshapes the social structure of society. The result of this research is that according to Simmel, conflicts that violate the tradition of prohibiting semarga marriages in the Batak tradition in Labuhan Batu Utara appear destructive, can actually strengthen social cohesion by affirming community norms and values, while creating space for individuals to show their identity and superiority in the larger social order. Conflicts arising from the clash between old traditions and new customs in Batak society in Labuhan Batu Utara show new customs where personal and family happiness are increasingly prioritized over the customary prohibition of semarga marriage. In this context, the flexibility of the Batak community in dealing with evolving social dynamics, adopting new customs that are more in line with the needs and aspirations of individuals and families today.